Optimization of hot air drying process for tiger nut and analysis of fatty acid composition of tiger nut oil - Li, He; Niu, Xiaoxiao; Chai, Jiajun; Guo, Changle; Sun, Yihao; Li, Jianhua; Li, Chunying (International Journal of Agricultural and Biological Engineering, 2021)
Hot air temperature, hot air humidity, and hot wind speed were selected as independent variables of quadratic orthogonal rotation combination test design through single factor test. Drying time, energy consumption, chromatism value, luminosity value, hardness, rehydration ratio, and other indexes of the product were used as the response value of the test. Response surface methodology (RSM) was used to analyze the effects of independent variables on the quality of tiger nut (Cyperus esculentus L.), and the process parameters were combined and optimized. The results show that the suitable technological conditions for hot air drying of tiger nut are as follows: hot air temperature of 63.15°C, hot air humidity of 44.92%, hot air wind speed of 2.48 m/s. Under these conditions, the product has the advantages of the short drying cycle, low energy consumption, good color and luster, low hardness and good rehydration performance. The fatty acid composition and content of tiger nut oil were determined by gas chromatography. The fatty acid composition and content of tiger nut oil were compared with those of soybean oil, olive oil, rapeseed oil and sesame oil, the results show that among the saturated fatty acids in tiger nut oil, palm oil had the highest content of 11.172%, which was between soybean oil and olive oil. The main composition of unsaturated fatty acids in tiger nut oil is oleic acid, with a content of 77.605%, which is 3.6 times higher than that of soybean oil, and even higher than that of olive oil. Keywords: process optimization, tiger nut, hot air drying, fatty acid composition, oil response surface method DOI: 10.25165/j.ijabe.20211406.6646 Citation: Li H, Niu X X, Chai J J, Guo C L, Sun Y H, Li J H, et al. Optimization of hot air drying process for tiger nut and analysis of fatty acid composition of tiger nut oil. Int J Agric & Biol Eng, 2021; 14(6): 228–236.